BRASH Syndrome in the Absence of Chronic Kidney Disease: A Case Report - Anthony Zaffino; Amanda Polsinelli; Adam Purdy (Clinical Practice and Cases in Emergency Medicine)
Introduction: Bradycardia, Renal failure, Atrioventricular nodal blockade, Shock, Hyperkalemia (BRASH syndrome) is commonly misdiagnosed in the emergency department, which can lead to a delay in care and poor patient outcomes. Case Report: We present a case of BRASH syndrome in a patient with no underlying renal disease, which further complicated diagnosis and delayed treatment. Conclusion: Prompt recognition of the underlying pathophysiology in cases of BRASH syndrome is essential to guide treatment and avoid delays in care.